2006
DOI: 10.1097/01.ta.0000214580.27501.19
|View full text |Cite
|
Sign up to set email alerts
|

Body Composition Changes with Time in Pediatric Burn Patients

Abstract: Body composition of severely burned children significantly improved in the second year compared with the first year after injury. This demonstrates a need for long-term rehabilitation in these burn patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
92
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 102 publications
(93 citation statements)
references
References 8 publications
(14 reference statements)
1
92
0
Order By: Relevance
“…We have shown that loss of proteins, muscle, and bone persists up to 2 years postburn affecting patients' lives remarkably. 1,2 We, therefore, suggest that it is beneficial to attenuate the hypermetabolic response immediately postburn and subsequently preserve protein and amino acid stores. Agents known to affect postburn hypermetabolism and catabolism are insulin, IGF-I, oxandrolone, GH, and propranolol.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…We have shown that loss of proteins, muscle, and bone persists up to 2 years postburn affecting patients' lives remarkably. 1,2 We, therefore, suggest that it is beneficial to attenuate the hypermetabolic response immediately postburn and subsequently preserve protein and amino acid stores. Agents known to affect postburn hypermetabolism and catabolism are insulin, IGF-I, oxandrolone, GH, and propranolol.…”
Section: Discussionmentioning
confidence: 99%
“…A hologic model QDR-4500W DEXA (Hologic Inc, Waltham, MA) was used to determine body composition as previously published. 1,2,18,19 Hormones, proteins, and cytokines Blood and/or urine was collected from burn patients at admission, pre-operatively, and 5 days post-operatively for 4 weeks for serum hormone, protein, cytokine and urine hormone analysis. Blood was drawn in a serum-separator collection tube and centrifuged for 10 minutes at 1320 rpm; the serum was removed and stored at −70°C until assayed.…”
Section: Body Compositionmentioning
confidence: 99%
See 3 more Smart Citations